CULTURE, CULTURE LEARNING AND NEW TECHNOLOGIES: TOWARDS A PEDAGOGICAL FRAMEWORK - Mike Levy (Language Learning and Technology, 2007)
This paper seeks to improve approaches to the learning and teaching of culture using new technologies by relating the key qualities and dimensions of the culture concept to elements within a pedagogical framework. In Part One, five facets of the culture concept are developed: culture as elemental; culture as relative; culture as group membership; culture as contested; and culture as individual (variable and multiple). Each perspective aims to provide a focus for thinking about culture, and thereby to provide a valid and useful point of departure for thinking about the practice of culture learning and teaching with new technologies. The referenced literature draws from a broad range of disciplines and definitions of culture. In Part Two, five projects are chosen to represent relevant technologies currently in use for culture learning: e-mail, chat, a discussion forum and a Web-based project. Each project is used to illustrate facets of the culture concept discussed in Part One with a view to identifying key elements within a pedagogical framework that can help us respond effectively to the challenge of culture learning and teaching utilising new technologies. Thus the goal is to align fundamental qualities of the culture concept with specific pedagogical designs, tasks and technologies.